Merangkul Cina hubungan Indonesia-Cina pasca-Soeharto - Wibowo, I.; Hadi, Syamsul (Gramedia Pustaka Utama, 2009)
Foreign relations and economic relations between Indonesia and China after the Soeharto's government; papers of a seminar.